A nonsteroidal anti-inflammatory drug, zaltoprofen, inhibits the growth of extraskeletal chondrosarcoma cells by inducing PPARγ, p21, p27, and p53. Issue 8 (18th April 2023) - Higuchi, Takashi; Takeuchi, Akihiko; Munesue, Seiichi; Yamamoto, Norio; Hayashi, Katsuhiro; Harashima, Ai; Yamamoto, Yasuhiko; Tsuchiya, Hiroyuki
ABSTRACT: Peroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear receptor and master transcription factor of adipogenesis-related genes, and has been reported as an antitumor target for chondrosarcomas. Herein, we show that the nonsteroidal anti-inflammatory drug, zaltoprofen, induces the expression of PPARγ at the mRNA and protein levels, following the induction of PPARγ-activating factors, such as Krox20, C/EBPβ, and C/EBPα, in human extraskeletal chondrosarcoma H-EMC-SS cells. Upregulation of the cell cycle checkpoint proteins, p21, p27, and p53, was observed upon treatment of H-EMC-SS cells with zaltoprofen, which probably resulted in the inhibition of proliferation of these cells observed in vitro . Zaltoprofen treatment inhibited tumor growth, induced tumor cell apoptosis, and was well tolerated in a mouse model of extraskeletal myxoid chondrosarcoma. Our results provide mechanistic insights into the therapeutic effect of zaltoprofen that should promote further studies on the rational use of this drug for the effective treatment of sarcomas.